Review on static component generation of ultrasonic waves in solid media - Xiang Wan; Shuaixiang Chen; Liping Huang; Xuhui Zhang; Xiangang Cao; Yuan Chen (AIP Advances)
In nonlinear ultrasonics (NLU), in addition to the well-known second harmonic generation (SHG), a static component (SC) generation occurs when a primary ultrasonic wave propagates through a solid with quadratic elastic nonlinearity. The generation of SC does not need to satisfy the phase velocity matching condition requested for SHG. Despite SC’s inherent advantages, previous reviews on NLU have frequently overlooked this nonlinear phenomenon. This paper presents a comprehensive review on the SC generation when ultrasonic waves propagate in solid media. The theoretical analysis of SC generation from primary longitudinal waves and primary Lamb waves in an isotropic plate is elaborated in detail without considering the attenuation effects. The propagation characteristics of SC from primary longitudinal waves, Lamb waves in plates, and ultrasonic guided waves (UGWs) in pipe-like structures are elucidated. The experimental reception and measurement techniques of SC are discussed. The application of SC in evaluating microscale damage in various fields is presented. Conclusions and future perspectives are summarized at the end of this review.